Impact of Social Network Sites in the Life of University Students: A Case Study of Pokhara University, Nepal (International Journal of Innovative Research in Computer Science & Technology, 2021)
This work analyses the impact of social  network sites on the life of a university student in terms of  intensity of use, personal life satisfaction, social trust, social  expression and physical health. Study is based on close end  survey design and consists of one hundred and fifty-four  (154) respondents of four constituent campuses of Pokhara  University, Nepal. The study uses both descriptive and  inferential statistical methods to analyze data, draw  conclusions and forward recommendations of the study.  Chi-square test is also performed on the identified variables  under investigation to calculate association among them.  The work summarizes both the positive as well as negative  aspects of using social network sites on the life university  students that helps to build an understanding of role of  technology in their life. Further, this study can serve as a  base in identifying the socio-psychological aspects of  technology of human life. For universities of under  developed countries like Nepal, this can be a vital study in  understanding technology and its application in academia.
Keywords: Social networking sites; Intensity of use; Physical health; Personal life satisfaction; Social trust; Social learning; Social expression